Metaphorical use of the lexeme "theater" in the publicistic style of the modern Russian language - Ermolova, Karina Andreevna (Litera, 2025)
The aim of the paper is to investigate the main mechanisms of metaphorization of the lexeme "theater", which are expressed in the meaning of linguistic units and in the speech utterance. The article explores the features of metaphorical use of the lexeme "theater" in the journalistic style, this issue is considered through the prism of figurative means characteristic of the Russian language. The topic of this study is relevant, because modern philologists pay special attention to the issue of metaphorical interpretation of the Russian language lexicon and study the features of linguistic representation of the metaphorical potential of the national lexicon through figurative means. The research is based on the cognitive and linguocultural approach to the study of metaphorical potential of speech and language. Methods: contextual and structural-semantic analysis. The material for the study were the contexts in which the metaphorical potential of the lexeme "theater" is displayed. 300 contexts from the National Corpus of the Russian Language, borrowed from modern Russian-language mass media - newspapers and magazines - were studied in total. The scientific novelty of the work consists in identifying the specifics of metaphorization of the most important qualities and properties of the theater, expressed through speech utterances and through the semantics of linguistic units, on the example of the modern language of mass media - newspapers and magazines. In the course of the study it was established that the metaphorical functioning of the lexeme "theater" in the journalistic style is based on such initial features as pretense (falsity), spectacle (theatrical action), play, life (imitation, model of real life). There is a metaphorical projection of these qualities onto the properties of objects having material and immaterial character: human thinking and social activity (theater as a kind of activity, a kind of professional occupation of a person), place (theater as "the world on the contrary", as "looking-glass" - a place where everything is different from the real world), human qualities (pretension, deceitfulness, the desire to boast, the desire to live and act "for show"), process (dynamically changing life, which has a cyclical character: birth - development - death), result (theater as a "show"), process (dynamic life, which has a cyclical character: birth - development - death). The results of the study allow us to reconstruct a significant fragment of the Russian-language picture of the world in the axiological and cognitive aspect. The data of the study of modern periodicals devoted to the theater allow us to conclude about the important role of the lexeme "theater" in the metaphorical thinking of the Russian-speaking person.